Up From the Ashes: Age and Gender Effects on Post-Traumatic Growth in Bereavement. Issue 3 (2nd July 2016) - Patrick, Julie Hicks; Henrie, James
Abstract : Researchers and clinicians are increasingly exploring the predictors and moderators of posttraumatic growth. To date, however, no studies have fully examined the interactive effects of age and gender in grief and post-traumatic growth. To that end, we examined the moderating effects of age and gender on the relations between grief and post-traumatic growth. A total of 414 adults, ages 18 to 66 years, who were bereaved for 2 years or less, completed a battery of self-report questionnaires. Results of a Gender (2) by Age (4) analysis of variance test showed few differences, overall. Small, significant gender differences were detected for current grief, with women expressing more grief than men. A main effect of age was also observed for grief, with emerging adults reporting less grief than middle-aged adults. A series of moderation models were conducted whereby the effects of gender and age on the relation between grief and post-traumatic growth were examined. Results showed small but significant moderation effects of gender, but not age. Results are discussed in terms of the need for more precision in the research examining post-traumatic growth, including the need for theoretical foundations rooted in both feminist and lifespan theories.